Exploring Collaborative Problem-Solving Competency of Junior High School Students - Friska Octavia Rosa; Arif Rahman Aththibby (Jurnal Pendidikan Fisika, 2021)
The 2013 curriculum implemented in the learning process demands students to be able to develop every aspect owned by each individual; one of them is Collaborative Problem Solving (CPS) competency. The global competition after finishing education is also a concern for learning outputs. Collaborative problem-solving does not only sharpen the students' cognitive competency but also their social attitude. Education is a process that involves students through their thinking to continue to innovate in order to solve the surrounding problems properly. Every time, it is necessary that students are prepared to obtain skills that they will need in the future. The purpose of this research is to analyze collaborative problem-solving skills in middle-level students. How these skills contribute towards students' understanding process on learning itself, both individually and in groups. This study was performed at a State Junior High School in Lampung during the odd semester of the 2019/2020 academic year. Samples used in this research were determined using random sampling techniques. The research sample was 63 students'. The instruments used in data collecting were observation, interview, and test, without any treatment towards the sample. The research data shows that the percentage of students' social skills has an average score in the low category (participation and perspective-taking), while all aspects of cognitive skills are in the low criteria (regulation, learning and knowledge building, and task regulation). Based on these results, it can be concluded that students' collaborative problem-solving skills are still in the low category, so further research needs to be carried out as an alternative that can be done to improve collaborative problem-solving skills.